Cutaneous sensory symptoms and emotional regulation in non-clinical healthy students: a near-infrared spectroscopy study - Ozawa, Sachiyo; Yoshimoto, Hiromasa; Tanabe, Hajime; Koike, Shinsuke (Frontiers in Psychology, 2025)
BackgroundIn an era of increasing societal stress, greater attention must be given to the mental health and well-being of non-clinical populations. Many individuals in these groups report cutaneous sensory symptoms—such as pain, crawling sensations, and burning—linked to underlying mental stress. To investigate the relationship between these stress indicators and well-being, this study examines whether university students with higher versus lower levels of these symptoms differ in their ability to regulate emotions through distraction.MethodsData were collected from 57 university students (mean age: 19.26 ± 1.03 years, range: 18–23 years, 22 males), including near-infrared spectroscopy (NIRS) data from 53 participants. Students were categorized into higher (n = 21) and lower (n = 36) cutaneous symptom groups based on the mean Cutaneous9 score. In the experiment, the participants first rated their Cutaneous9 symptoms, then completed an emotion-induction task by recalling stressful interpersonal events. Next, they performed the Sustained Attention to Response Tasks (SART) as a distraction. The SART is a type of go/no-go task that includes spontaneous thought probes at pseudo-random intervals to assess attentional state or degree of off-task thoughts. Prefrontal activity during the SART was assessed using NIRS. Emotional states were assessed before induction, after induction, and after distraction using the Positive and Negative Affect Schedule.ResultsParticipants with higher cutaneous symptoms struggled more with maintaining attention during SART and showed less reduction in unpleasant emotions. Only those with lower symptoms experienced a decrease in unpleasant emotions. Furthermore, participants with higher cutaneous symptoms exhibited medial prefrontal cortex activation during distraction, with no significant activation differences in the lateral prefrontal cortex.ConclusionThese findings suggest that university students with higher cutaneous symptoms face greater challenges in regulating emotions compared with those with lower symptoms. Their reduced ability to benefit from distraction may stem from difficulties in maintaining attentional focus or increased absorption in off-task thoughts, rather than impaired emotional inhibition. Addressing these challenges through targeted interventions may enhance the mental well-being and overall quality of life in non-clinical populations.